2015
DOI: 10.1016/j.celrep.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Rheb Inhibits Protein Synthesis by Activating the PERK-eIF2α Signaling Cascade

Abstract: SUMMARY Rheb, a ubiquitous small GTPase, is well known to bind and activate mTOR, which augments protein synthesis. Inhibition of protein synthesis is also physiologically regulated. Thus, with cell stress the unfolded protein response system leads to phosphorylation of the initiation factor eIF2α and arrest of protein synthesis. We now demonstrate a major role for Rheb in inhibiting protein synthesis through enhancing the phosphorylation of eIF2α by protein kinase-like endoplasmic reticulum kinase (PERK). Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Our work demonstrates that AKT inactivation represents a major mechanism that induces the PERK-eIF2aS51P arm in TSC-deficient cells by ER stress. Nevertheless, additional mechanisms cannot be excluded as for example the ability of Rheb GTPase to physically interact with and activate PERK (50). We also demonstrate that an important property of mTORC2 inactivation is the activation of PERK and induction of eIF2aS51P, which represents a prosurvival mechanism used by TSC-deficient cells to counteract the deleterious effects of ER stress (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Our work demonstrates that AKT inactivation represents a major mechanism that induces the PERK-eIF2aS51P arm in TSC-deficient cells by ER stress. Nevertheless, additional mechanisms cannot be excluded as for example the ability of Rheb GTPase to physically interact with and activate PERK (50). We also demonstrate that an important property of mTORC2 inactivation is the activation of PERK and induction of eIF2aS51P, which represents a prosurvival mechanism used by TSC-deficient cells to counteract the deleterious effects of ER stress (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…viral infection, nutrient and heme-deprivation, [23]. In addition to these other mechanisms it has recently been reported that RHEB GTPase which stimulates mTOR activity also phosphorylates eIF2α attenuating protein translation [24]. Thus, when mTOR is shut down either by FF + 2-DG or rapamycin, RHEB may be playing a role in the increased phosphorylation we detect in eIF2α which may not necessarily reflect increased ER stress.…”
Section: Discussionmentioning
confidence: 87%
“…Rheb-PERK signaling is activated under ER stress leading to inhibition of protein synthesis, indicating that Rheb may function as a molecular switch between stimulation and inhibition of protein synthesis under physiological as well as pathological conditions (Tyagi et al, 2015).…”
Section: Response To Other Stressesmentioning
confidence: 99%
“…Although in general, Rheb-mTORC1 signaling promotes protein synthesis, recently, it was reported that Rheb inhibits protein synthesis by mediating phosphorylation of eukaryotic initiation factor 2α (eiF2α) via PERK independent of mTORC1 signaling (Tyagi et al, 2015). Rheb-PERK signaling is activated under ER stress leading to inhibition of protein synthesis, indicating that Rheb may function as a molecular switch between stimulation and inhibition of protein synthesis under physiological as well as pathological conditions (Tyagi et al, 2015).…”
Section: Response To Other Stressesmentioning
confidence: 99%
See 1 more Smart Citation